Courage of Uzbeks on the Battlefields - Jumaboyeva; Akhtamova Khurshida Jamshid; Borikulova; Islam Muhammadiyev (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
World War II is one of the greatest tragedies in human history. 72 countries of the world joined this war, and 110 million people were mobilized into their armies. During the war, about 55 million people were killed, thousands of cities and villages, factories and factories, cultural monuments, communication and irrigation facilities were destroyed. The total amount of damages and expenses is 4 trillion. made up the dollar. Here the question arises: what are the reasons for the start of the Second World War? Is it preventable, or does it inevitably start? It is possible to answer this question based on the analysis of the social, political and economic situation in the world in the 30s of the 20th century.